Direct to angiography suite approaches for the triage of suspected acute stroke patients: a systematic review and meta-analysis. (February 2022) - Brehm, Alex; Tsogkas, Ioannis; Ospel, Johanna M.; Appenzeller-Herzog, Christian; Aoki, Junya; Kimura, Kazumi; Pfaff, Johannes A.R.; Möhlenbruch, Markus A.; Requena, Manuel; Ribo, Marc J.; Sarraj, Amrou; Spiotta, Alejandro M.; et al.
Background: Increasing evidence suggests improved time metrics leading to better clinical outcomes when stroke patients with suspected large vessel occlusion (LVO) are transferred directly to the angiography suite (DTAS) compared with cross-sectional imaging followed by transfer to the angiography suite. We performed a systematic review and meta-analysis on the efficacy and safety of DTAS approaches. Methods: We searched Embase, Medline, Scopus, and clinicaltrials.gov for studies comparing outcomes of DTAS and conventional triage. Eligible studies were assessed for risk of bias. We performed a random-effects meta-analysis on the differences of median door-to-groin and door-to-reperfusion times between intervention and control group. Secondary outcomes included good outcome at 90 days (modified Rankin Scale ⩽ 2) rate of symptomatic intracranial hemorrhage (sICH) and mortality within 90 days. Results: Eight studies (one randomized, one cluster-randomized trial and six observational studies) with 1938 patients were included. Door-to-groin and door-to-reperfusion times in the intervention group were on median 29.0 min [95% confidence interval (CI): 14.3–43.6; p  < 0.001] and 32.1 min (95% CI: 15.1–49.1; p  < 0.001) shorter compared with controls. Prespecified subgroup analyses for transfer ( n  = 1753) and mothership patients ( n  = 185) showed similar reductions of the door-to-groin and door-to-reperfusion times in response to the intervention. The odds of good outcome did not differ significantly between both groups but were numerically higher in the intervention group (odds ratio: 1.38, 95% CI: 0.97–1.95; p  = 0.07). There was no significant difference for mortality and sICH between the groups. Conclusion: DTAS approaches for the triage of suspected LVO patients led to a significant reduction in door-to-groin and door-to-reperfusion times but an effect on functional outcome was not detected. The subgroup analysis showed similar results for transfer and mothership patients. Registration﻿: This study was registered in PROSPERO (CRD42020213621).